Stereoselective Synthesis of Tricyclic Diproline Analogues that Mimic a PPII Helix: Structural Consequences of Ring‐Size Variation. Issue 29 (29th August 2014) - Soicke, Arne; Reuter, Cédric; Winter, Matthias; Neudörfl, Jörg‐Martin; Schlörer, Nils; Kühne, Ronald; Schmalz, Hans‐Günther
Abstract: Polycyclic proline‐derived scaffolds (ProMs) have recently demonstrated their value as conformationally defined dipeptide analogs for the modular construction of secondary structure mimetics, specifically interfering with PPII helix‐mediated protein–protein interactions. We disclose the stereoselective synthesis of two new tricyclic amino acid scaffolds (ProM‐4 and ProM‐8) that differ from the first generation scaffold ProM‐1 by the size of ring A. Conformational preferences and subtle structural differences of the three homologous scaffolds were analyzed by X‐ray crystallography, computational calculations, and NMR spectroscopy. N ‐ tert ‐butoxycarbonyl(Boc)‐3‐(1‐propenyl)azetidine‐2‐carboxylic acid was prepared fromL ‐aspartic acid through β‐lactam intermediates. The corresponding piperidine‐based building block rac ‐ N ‐Boc‐3‐vinylpipecolic acid was synthesized by Cu‐catalyzed 1, 4‐addition of vinyl‐MgBr to methyl N ‐Boc‐2, 3‐dehydropipecolate. Target molecules were prepared through peptide coupling of the respective ring A building blocks with cis ‐5‐vinylproline tert ‐butyl ester and subsequent ring‐closing metathesis. Selective deprotection of a tert ‐butyl carbamate ( N ‐Boc protecting group) in the presence of a tert ‐butyl ester was achieved with trifluoroacetic acid at 0 °C. Abstract : Two new tricyclic amino acid scaffolds, which differ from the first generation scaffold by the size of ring A, were stereoselectively synthesized. The conformational analysis of the three homologous scaffolds was revealed by NMR spectroscopy.